2016
DOI: 10.1590/1807-1929/agriambi.v20n11p955-959
|View full text |Cite
|
Sign up to set email alerts
|

Use of mulches and their effects on the radish crop

Abstract: A B S T R A C TThis work aimed to evaluate the influence of green fertilization and the compost on the production of radish, cv. 'Cometa' . The experimental design was randomized blocks with 6 treatments and 4 replicates: T1 -Leucaena, T2 -'Madeira-nova' , T3 -Compost (maize straw and composted cattle manure), T4 -'Sempre verde' grass + compost and T5 -'Sempre verde' grass and T6 -control without fertilization, totaling 24 experimental plots. The total area of the experimental plot was 1.44 m 2 , with useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
0
0
3
Order By: Relevance
“…Comparing the results of this study with published literature, several studies have reported the positive effects of organic fertilizers, such as water hyacinth organic fertilizer, on plant growth and nutrient availability (Santos et al, 2016;Duong et al, 2019). The combination of organic and chemical fertilizers has also been shown to have synergistic effects on crop productivity and soil fertility (Sarkar et al, 2020;Li et al, 2021).…”
Section: Root Diametersupporting
confidence: 66%
“…Comparing the results of this study with published literature, several studies have reported the positive effects of organic fertilizers, such as water hyacinth organic fertilizer, on plant growth and nutrient availability (Santos et al, 2016;Duong et al, 2019). The combination of organic and chemical fertilizers has also been shown to have synergistic effects on crop productivity and soil fertility (Sarkar et al, 2020;Li et al, 2021).…”
Section: Root Diametersupporting
confidence: 66%
“…O índice de clorofila não apresentou em nenhum ciclo diferenças significativas entre os tratamentos avaliados. Santos et al (2016) estudando a influência de adubos verdes e composto no desenvolvimento do rabanete encontraram o valor máximo do índice SPAD de clorofila de 33,55, sendo inferior ao do presente estudo que variou de 36,55 a 45,47 nos três ciclos de cultivo.…”
Section: Resultsunclassified
“…As avaliações foram realizadas com trinta dias, as variáveis analisadas sobre o crescimento foram diâmetro de caule: com auxílio de paquímetro fizemos a medição no colo da planta de cada parcela, área foliar: com auxílio de régua padrão obtivemos a largura e comprimento de uma folha de cada parcela, com a multiplicação de ambos juntamente com o fato de correção do rabanete 0,57 de acordo com Santos et al (2016), número de folhascontagem do total de folhas de cada planta na parcela, altura de plantarégua padrão com a medição do colo da planta até a folha mais alta, em cada parcela.…”
Section: Metodologiaunclassified